Geographic distribution of two mussel species and associated assemblages along the northern Argentinean coast - Arribas, Lorena Pilar (2013)
Ecosystem engineers can modify habitat, creating structural microhabitats. This structural complexity can affect species richness. Marine ecosystem engineers are able to produce local effects in combination with environmental variables (e.g. to create more humid habitat during low tides). We tested the hypotheses that if there is a relationship between mussel morphology and environmental factors, mussels would be larger at warmer than at cooler locations, and in areas where 2 species of mussels overlap, size and biomass will decrease and density will increase. At a smaller scale, we predicted that there is a relationship between the assemblage structure and hardness of the substratum and sediment content of a mussel bed. Using a nested design, we measured density, biomass and size of 2 species of mussels, Brachidontes rodriguezii and Perumytilus (Brachidontes) purpuratus, and diversity of species associated with mussel beds at 2 rocky intertidal sites at each of 4 shores along the northern Argentinean coast. These variables were correlated with oceanographic conditions and local characteristics. Significant correlations were found between intertidal assemblages and local factors. The largest specimens of B. rodriguezii and P. purpuratus were found at the warmer shores. In areas where they overlapped, size, biomass and density of P. purpuratus were lower, although B. rodriguezii did not change. The mean abundance of invertebrates associated with a mussel bed showed significant differences among shores. These 2 species of mytilids coexist over a small area, and although these species are very similar in their biological and ecological function, the fauna associated with their matrices are very different.